Correlation between Serum High-Sensitivity C-Reactive Protein Level and Severity of Albuminuria Measured by Urine Albumin-to-Creatinine Ratio in Type 2 Diabetic Patients - Febrianto, Dicky; Soelistijo, Soebagijo Adi; Tjempakasari, Artaria (Current Internal Medicine Research and Practice Surabaya Journal, 2023)
Introduction: One of complications in type 2 diabetes mellitus (DM) that require high treatment cost is diabetic kidney disease (DKD), which is characterized by the presence of albuminuria, decrease in glomerular filtration rate, or both. Researches show a positive correlation between type 2 DM and serum high-sensitivity C-reactive protein (hs-CRP) level, a sensitive marker of subclinical inflammation. This study aimed to analyze the correlation between serum hs-CRP level and severity of albuminuria measured by urine albumin-to-creatinine ratio (ACR).Methods: The study was conducted at the Endocrinology Outpatient Clinic of Dr. Soetomo General Academic Hospital, Surabaya, on June-July 2020.Results: The study included 50 patients with type 2 DM, consisting of 25 (50%) men and 25 (50%) women, with median age of 58.0 (42-68) years and mean body mass index (BMI) of 21.91 ± 1.310 kg/m2. Median duration of DM was 12.0 (6-22) years, median HbA1c level was 7.20% (5.7%-12.3%), mean serum crEatinine level was 0.83 ± 0.180 mg/dL, and median estimated glomerular filtration rate (eGFR) value was 92.85 (61.6-121.2) mL/minute/1.73 m2. Median serum hs-CRP level was 1.20 (0.1-4.0) mg/L and median urine ACR value was 49.570 (7.78-426.00) mg/g. Normoalbuminuria was detected in 28% of subjects, microalbuminuria in 66% of subjects, and macroalbuminuria in 6% of subjects. This study showed positive and significant correlation between serum hs-CRP level and severity of albuminuria (r = 0.701; p = <0.001).Conclusion: There was positive and significant correlation betweeen serum hs-CRP level and severity of albuminuria in type 2 diabetic patients.